An Assessment of Bird Diversity Around Joshimath Nanda Devi Biosphere Reserve, Uttarakhand - Jan, Rohi; Uniyal, V. P.; Chauhan, Anita (Indian Forester, 2011)
Assessment of bird diversity has been conducted in different forest types (conifer, oak, mixed) and human settlement and area around Joshimath, the buffer zone of Nanda Devi Biosphere Reserve. Point count transect and line transect method were applied for bird survey. Dominance was found to be higher in conifer patch. Species evenness was found in human habitation which is in accordance with middisturbance hypothesis. Kail (Pinus wallichiana) was dominant tree-species in all the habitats. The study recorded 95 bird with the one vulnerable species Cheer Pheasant (Catreus wallichii). The study recommends for sound conservation management practices in and around the buffer area as it was a good repository of bird diversity of the entire biosphere reserve.